Muna Local Food Defense Post-Arrival of Transmigrants in South Tiworo Subdistrict West Muna Regency - Mursin, Mursin; Suyyuti, Nasruddin; Sifatu, Wa Ode Sifatu (Universitas Halu Oleo, 2020)
The purpose of this study was to reveal the pattern of Muna's local food sustainability, and the response of transmigrant communities to Muna's local food. The theory used in this research was Geertz's mindset, Clifford (1973) about ethos, world-view, and the Analysis of sacred symbols with ethnographic methods . Research Results showed that: 1) The pattern of local food security of the Muna community through: at least every planting season there are three types of plants: rice, corn, sweet potatoes, cassava, and vegetables. Every day, there are at least five types of food: rice, processed corn, processed cassava, vegetables, and side dishes, as well as completing the life cycle ceremony. Local food of the Muna community can disappear if it eliminates the life cycle ceremony because of the influence of the new Islamic religion. In the development of leaves as the staple of vegetables, they have health functions. Muna's local food that still survives today is cahitela, paewuna, mafusau, midawa, ghofa, mafu, tonea, rapo-rapo, bhanggai, romedawa, popasa, ghontoghe, usa, ghoenu, lembeghu, wuragha, robu, foo, paranggi, sirikaea, bubuno, katapi, kahawa, pumpkin, ghotimu, conduru, pariah, tereka, kula, lawue, kentanooemorindi, kenta we tehi ,, kaliwuoemorindi, kaliwu we tehi. 2) Transmigrants also participate in consuming local Muna food. Conclusion: The work ethic and farming patterns that are still maintained up to the new Islamic religious school faced by the Muna community in maintaining local food. As a result, a relative of the Muna community could have a conflict just because of the implementation of a life cycle ceremony. The government should be able to revive the use of local food in a scientific way.Â Keywords: Defense, Local Food, Transmigrants